Financial Ratios and Tax Awareness of Indonesian Companies - Syafii Syafii; Aliffianti Safiria Ayu Ditta; Dien Ajeng Fauziah; Khoirul Abidin (AKRUAL: JURNAL AKUNTANSI, 2026)
Introduction/Main Objectives: This study examines the relationship between corporate financial ratios and tax awareness, emphasizing nationalism. Background Problems: The paper addresses the issue of corporate tax awareness and its impact on tax compliance. The central research question is: "How do corporate financial ratios influence tax awareness and compliance in Indonesian public companies?" Novelty: This study provides a unique, long-term analysis of the connection between financial performance and tax behavior, utilizing advanced econometric methods. It fills a gap in the literature where previous research has not comprehensively examined this relationship within the specific context of Indonesian firms. Research Methods: The Generalized Method of Moments (GMM) method is used to address endogeneity issues in the research model. The study analyzes Gross Profit Margin (GPM), Operating Profit Margin (OPM), Pretax Profit Margin (PPM), Corporate Tax to Turn Over Ratio (CTTOR), and Net Profit Margin (NPM) using panel data from 2004 to 2024. Finding/Results: Results indicate a significant positive relationship between higher financial ratios and corporate tax awareness, suggesting that good financial performance is associated with high tax awareness and compliance. Additionally, responses to tax incentives significantly impact the potential for tax non-compliance. Conclusion: The study concludes that transparent financial reporting and strong financial performance are essential for enhancing corporate tax awareness. Companies are advised to prepare transparent annual reports and comply with tax regulations to support national development and promote a fair and efficient tax system. The main takeaway is the importance of financial transparency in encouraging tax compliance.